Quality Service as A Strategy for Improving School Competitive Advantage - Rosi, Fathor; Hefniy, Hefniy; Widat, Faizatul; Aisyah, Siti; Munaamma, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This paper aims to find out about increasing the competitive advantage of schools through optimizing service quality at RA Perwanida 2 Probolinggo. A qualitative method with a case study approach is used to understand the research objectives. Data collection techniques used are interviews, observation, and documentation. The data analysis used is theme analysis, which focuses on essential issues in understanding the case's complexity. The results of the study show that increasing the competitive advantage of schools through optimizing service quality is carried out through; transformative principal leadership, analyzing student service needs, building a quality culture consisting of several stages; 1) formulate standards of attitude and behavior of school residents; 2) formulate service standards; and 3) motivating school members, conducting regular in-service training, and providing rewards and punishments. This research has implications for the importance of service quality for schools to build public trust so that people will believe in the quality provided by schools.